PENGARUH MEDIA PUZZLE TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA DI KELAS III SD NEGERI 155 INPRES GALESONG - Hajrawati; Andi Husniati; Kristiawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
HAJRAWATI. 2026. The Effect of Puzzle Media on Student Learning Outcomes in Mathematics Learning in Grade III of SD Negeri 155 Inpres Galesong. Thesis. Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. Supervised by Andi Husniati and Kristiawati. This study aims to determine the effect of using puzzle media on students' mathematics learning outcomes on fractions in grade III of SD Negeri 155 Inpres Galesong. The type of research used is a pre-experimental study with a One Group Pretest-Posttest Design. The population in this study were all 25 grade III students of SD Negeri 155 Inpres Galesong, consisting of 17 female students and 8 male students. The research sample was all 25 grade III students. The sampling technique used a saturated sampling technique, namely the entire population was used as the research sample. The instruments used in this study included learning outcome tests in the form of pretests and posttests to measure improvements in student learning outcomes, as well as documentation to support the research data. Data analysis was conducted using descriptive statistics and inferential statistics using a paired t-test. The results showed that the average pretest score for students was 57.20, categorized as low, while the average posttest score increased to 85.44, categorized as high. Hypothesis testing was conducted using a paired sample t-test. Based on the analysis using the paired sample t-test, the calculated t-value was -13.034 with a significance value (Sig. 2-tailed) of 0.000. The t-table value at a significance level of α = 0.05 with df = 24 degrees of freedom was 2.064. Since the calculated t-value = -13.034 > t-table = 2.064 and the significance value of 0.000 < 0.05, H₀ is rejected and H₁ is accepted. Thus, it can be concluded that the use of puzzle media has a significant influence on students' mathematics learning outcomes on fraction material in class III of SD Negeri 155 Inpres Galesong."